Efficiency in e-learning: Can learning outcomes be improved by using social networks of trainees and tutors? - Maglajlic, S.; Guetl, Christian (IEEE, 2012)
This article investigates improvements in the learning performance of trainees involved in an E-Learning programme in an industrial setting. To measure efficiency in E-Learning, our research develops a learning improvement indicator, defined as the difference in the learning outcome of a trainee before and after a certain period of time. The learning outcome, concretely, is measured by the test results of the trainees. In this regard, the test results should be evaluated both before and after taking the E-Learning course and / or before and after applying a specific action in the E-Learning environment. The experimental results in our industrial setting have indicated that there is room for improvement in the trainees' learning outcomes. We investigated the social networks that are implicitly formed by trainees and trainers in the E-Learning environment. The position of the trainee in these implicit social networks of the E-Learning setup proves to be correlated with the learning outcome. Methods that can improve the learning outcome by using the implicit social networks of trainees and tutors, as well as using social network engineering in order to influence the learning outcome - by placing the trainee in the appropriate position in the social network - are currently being investigated. In this research we provide an overview of the results gathered until now and propose a framework for future discussion.